An investigation on sliding wear behavior of PVD coatings - Costa, M. Y. P. [UNESP]; Cioffi, M. O. H. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Guimaraes, V. A. [UNESP] (Elsevier B.V., 2010)
Ti-6Al-4V alloy rubbing against aluminum-bronze 630 was evaluated in this work. High velocity oxygen fuel (HVOF) WC-10%Co-4%Cr thermal sprayed and TiN, CrN and DLC physical vapor deposition (PVD) coatings were applied to increase titanium substrate wear resistance. Pin-on-disk tests were performed with a normal force of 5 N and at a speed of 0.5 m/s, with a quantitative comparison between the five conditions studied. Results showed higher wear resistance for Ti-6Al-4V alloy DLC coated and aluminum-bronze 630 tribological pair and that the presence of graphite carbon structure acting as solid lubricant was the main wear preventing mechanism. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Sliding wear; Coating; Titanium alloy; Aluminum bronze